Description of eggs and nymphal instars of Triatoma baratai Carcavallo & Jurberg, 2000 based on optical and scanning electron microscopy (Hemiptera: Reduviidae: Triatominae) - Rocha, Dayse S.; Jurberg, Jose; Da Rosa, Joao Aristeu [UNESP]; Schaefer, Carl W.; Galvao, Cleber (Magnolia Press, 2009)
Triatoma baratai Carcavallo & Jurberg, is a wild (i. e., nonperidomestic) species found in the State of Mato Grosso do Sul (Bodoquena region, county of Bonito), Brazil. Its eggs and nymphs are described here based on optical and scanning electron microscopy. The operculum and exochorion have pentagonal, hexagonal, and heptagonal cells, with small cracks and small random pits. Differences in the eggs and five nymphal instars of T. baratai allow them to be distinguished from the sympatric species Triatoma williami Galvao, Souza & Lima, and from six of the nine members of the Triatoma oliveirai complex. The most useful differentiating characters are in the color, shape of the abdomen, head, and total body length. Keys are provided to separate the eggs and nymphal instars of six of the nine members of the Triatoma oliveirai species complex.
Keywords: Triatoma baratai; nymphs; eggs; external morphology; Chagas disease; keys